2015
DOI: 10.3349/ymj.2015.56.6.1572
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Accelerates the Degradation of Extracellular Matrix in Rat Hepatic Cirrhosis via Down-Regulation of Transforming Growth Factor-β1

Abstract: PurposeThe degradation of the extracellular matrix has been shown to play an important role in the treatment of hepatic cirrhosis. In this study, the effect of thalidomide on the degradation of extracellular matrix was evaluated in a rat model of hepatic cirrhosis.Materials and MethodsCirrhosis was induced in Wistar rats by intraperitoneal injection of carbon tetrachloride (CCl4) three times weekly for 8 weeks. Then CCl4 was discontinued and thalidomide (100 mg/kg) or its vehicle was administered daily by gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Apart from anti‐inflammatory and immunoregulatory effects, thalidomide also shows antiangioproliferative properties 12–14 . Thalidomide seems to exert and regulate the expression and synthesis of vascular endothelial growth factor, transforming growth factor β (TGF‐β) and α‐smooth muscle actin (α‐SMA) in other organ systems, such as liver and lung 15–17 . Such growth factors, along with androgens and inflammatory mediators, appear to be crucial regulators of prostate stromal cell growth 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from anti‐inflammatory and immunoregulatory effects, thalidomide also shows antiangioproliferative properties 12–14 . Thalidomide seems to exert and regulate the expression and synthesis of vascular endothelial growth factor, transforming growth factor β (TGF‐β) and α‐smooth muscle actin (α‐SMA) in other organ systems, such as liver and lung 15–17 . Such growth factors, along with androgens and inflammatory mediators, appear to be crucial regulators of prostate stromal cell growth 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide is a glutamic acid derivative with anti‐inflammatory, immunoregulatory, and antiangioproliferative properties 12–14 . Various effects of thalidomide have been discussed for decades, including its influence on myofibroblast differentiation 15–17 . Safe administration of thalidomide and its derivative, lenalidomide, for the treatment of erythema nodosum leprosum (ENL) or multiple myeloma is already possible and established 14,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…The latter bind reversibly to the active site of MMPs in a 1:1 molar ratio and, pathological imbalances in this system have been linked to the pathogenesis of hepatic fibrosis [ 17 , 18 ]. It has also been shown that the levels of TIMPs increase significantly by TGF-β, IL-6 and IL-22 in several in vitro and in vivo studies [ 16 , 50 , 51 ]. Alternately, treatment with IL-10 has been demonstrated to significantly increase the production of MMPs, including MMP-9, as well as significantly decrease TIMPs during liver fibrosis [ 7 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of IL-22 in the liver whether as inducer or suppressor of fibrosis is dependent on the etiology of hepatic disease [ 9 , 14 , 15 ]. Activated HSCs also express MMPs which are endopeptidases that play an important role in degradation and removal of all of the major components of the ECM [ 16 , 17 ]. The activity of MMPs is mainly regulated by tissue inhibitors of metalloproteinases (TIMPs) which are also secreted by the activated HSCs [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The placebo treatment also diminished the levels of ALT in CCl4-induced cirrhosis even after 4 weeks of discontinued induction ( 41 ). Besides, other authors reported that the spontaneous reversal of cirrhosis after 6 weeks of vehicle daily administration was accompanied by diminution of α-SMA positive cells and down-expression of TIMP-1, as well by up-expression of MMP-13 ( 42 ). In our study, drug therapy with doxazosin and BMP-7 showed greater recovery than spontaneous reversion, outstanding their promissory role in the treatment of fibrotic liver.…”
Section: Discussionmentioning
confidence: 99%